(untitled) (PJDOL, 2023)
The purpose of the study was to compare the efficiency of computerassisted (CA) phonological instructions on three levels of phonological awareness (PA) i.e. shallow, intermediate and deep on children and PA skill level comparison of hearing aid users and cochlear implant users. The study sample consisted of 40 children with age range 5-7 years, who used amplification devices in the form of a hearing aid and cochlear implant. While the selection criterion included a hearing age of three years